Transition disorder–order–disorder in reaction-diffusion biophysical system - V. V. Maksimov (Vestnik Samarskogo Gosudarstvennogo Tehničeskogo Universiteta. Seriâ: Fiziko-Matematičeskie Nauki, 2012)
The evolution of spatial pattern formation, which arises in the biophysical system of reaction-diffusion type in external noise, is researched analytically. The behavior of the probability density of the order parameter, its mean and the most probable values, susceptibility and second-order cumulant as a function of external noise intensity are studied in the statistically steady state. The boundary of transition “order-disorder” is defined. It is shown that there is a sequence of noise-induced ordering and disordering transitions in this system.